Eurasianism an ideology for the multipolar world - Pizzolo, Paolo (Russian, Eurasian, and Eastern European politics., 2019)
Eurasianism: An Ideology for the Multipolar World examines the ideology of Eurasianism - specifically neo-Eurasianist thought - and its implications for the international system.